Changes in atrial natriuretic peptide concentrations during intravenous saline infusion in hypoxic cor pulmonale. Issue 11 (November 1991) - Stewart, A G; Bardsley, P A; Baudouin, S V; Waterhouse, J C; Thompson, J S; Morice, A H; Howard, P
Abstract : BACKGROUND: The pathogenesis of oedema in hypoxic cor pulmonale is poorly understood. One possibility is a failure of atrial natriuretic peptide release, leading to salt and water retention. This hypothesis was tested by observing the response to an intravenous saline challenge in patients with and without cor pulmonale. METHODS: Plasma atrial natriuretic peptide concentrations were measured before and for three hours after an intravenous saline load (0.1 ml 2.7% saline/kg/min for 60 minutes) in 20 patients with chronic obstructive airways disease. Ten patients with cor pulmonale, as judged clinically by the presence of peripheral oedema with a previously documented increase in the jugular venous pressure or pleural effusions during an acute exacerbation of airway obstruction (mean (SE) age 67 (3) years, FEV1 0.73 (0.08) 1, arterial oxygen tension (PaO2) 6.4 (0.4) kPa, and arterial carbon dioxide tension (PaCO2) 6.7 (0.3) kPa), were compared with 10 patients with hypoxic chronic obstructive airways disease who had never had oedema (mean age 63 (1) years, FEV1 1.07 (0.09) 1, PaO2 8.6 (0.4) kPa, and PaCO2 5.3 (0.2) kPa). All patients were studied fasting and after diuretics had been stopped for three days. No supplemental oxygen was given. RESULTS: The mean four hourly urine sodium excretion was less in the patients who had oedema (27 (4.6) mmol, 13% of the intravenous load) than in those without oedema (82 (15.5) mmol, 43% of the load). Initial mean plasma atrial natriuretic peptide values were significantly higher in the patients with cor pulmonale (19.1 (1.6) compared with 10.2 (0.7) pmol/l) and the mean peak rise in atrial natriuretic peptide after the intravenous saline load had been given was 13 (8.0) pmol/l in the patients with cor pulmonale and 5.5 (2.3) pmol/l in the controls. There were no significant differences in plasma and urinary osmolality, blood pressure, or creatinine clearance between the groups. CONCLUSION: Patients with chronic obstructive airways disease and cor pulmonale have an impaired ability to excrete a hypertonic intravenous saline load despite a normal physiological release of plasma atrial natriuretic peptide.